b practical guide to implementing individualized intervention /c - Djabrayan.H, Jessica; Hannigan, J. E. (b, 2018)
Round out your school's PBIS system with this comprehensive guide. You've already established school-wide behaviour systems and developed solutions for at-risk students, now you'll implement effective interventions for students with the most challenging behaviour needs. Like companion volumes The PBIS Tier One Handbook and The PBIS Tier Two Handbook, this interactive resource takes you step by step through the implementation of intensive interventions within a multitiered system of support. Filled with practical examples, case scenarios, and rubrics, this book helps teams: identify students in need of Tier Three support; create procedures and protocols for students in both general education and special education; develop individualized interventions based on student needs and data. Students needing Tier Three help are few in number, but they can have the biggest impact on individual classrooms and school culture. By providing the intensive interventions students need in a systematic, thoughtful manner, you can improve outcomes for all students
Includes index.
Keywords: School psychology -- United States; Behavior modification -- United States; School children -- Discipline. -- United States; Students -- Psychology. -- United States; School management and organization -- United States